The methanolic extracts of Teucrium polium L. and Micromeria fruticosa (L.) Druce subsp. brachycalyx P. H. Davis improve diabetes in streptozotocin/nicotinamide-induced type 2 diabetic female Sprague Dawley rats - ÇAM, MUHAMMET EMİN; YAVUZ, AYŞE NUR; TAŞKIN, TURGUT; KABASAKAL, LEVENT; ELÇİOĞLU, HATİCE KÜBRA (My University, 2023)
Background: Teucrium polium and Micromeria fruticosa subspecies are known to be used in traditional medicine for diabetes treatment. Objective: The present study aimed to examine the potential antidiabetic effects and the mechanisms of antidiabetic actions of Teucrium polium L. methanolic extract (TP) and Micromeria fruticosa (L.) Druce subsp. brachycalyx P. H. Davis methanolic extract (MF) on rats with type 2 diabetes mellitus (DM). Methods: Streptozotocin (STZ) and nicotinamide (NA) were injected intraperitoneally to induce type 2 diabetes mellitus (T2DM) in rats. Plant extracts’ antidiabetic mechanisms of action were investigated with biochemical analyses and histopathological analyses performed. Results: TP and MF treatments reduced the blood glucose levels compared to the untreated diabetic rats. TP reduced TNF-α levels in serum, increased insulin levels in serum and pancreas, reduced SGLT-2 levels in kidneys, reduced GLUT-2 levels in the ileum; and MF reduced TNF-α levels, and increased insulin levels in serum and pancreas, increased GLP-1 levels, and reduced GLUT-2 levels in the ileum, and reduced SGLT-2 levels in kidneys. Treatments improved the histopathological results in the pancreas, kidney, and liver. Conclusions: The results presented in this study demonstrated that TP and MF both have potential antidiabetic effects and may be effective in T2DM treatment.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sosyal ve Beşeri Bilimler; Sosyoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Social Sciences and Humanities; Sociology; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; ENDOKRİNOLOJİ VE METABOLİZMA; TIP, GENEL & DAHİLİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; ENDOCRINOLOGY & METABOLISM; MEDICINE, GENERAL & INTERNAL; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Dahiliye; Endokrinoloji, Diyabet ve Metabolizma; Halk, Çevre ve İş Sağlığı; Internal Medicine; Endocrinology, Diabetes and Metabolism; Public Health, Environmental and Occupational Health; Antidiabetic; Medicinal plants; Micromeria fruticosa (L.) Druce subsp. brachycalyx P. H. Davis; Teucrium polium L.; Type 2 diabetes mellitus